Role of the cell membrane interface in modulating production and uptake of Alzheimer's beta amyloid protein - Bharadwaj, Prashant; Solomon, T.; Malajczuk, C.; Mancera, Ricardo; Howard, M.; Arrigan, Damien; Newsholme, Philip; Martins, R. (Elsevier, 2018)
© 2018 Elsevier B.V. The beta amyloid protein (Aß) plays a central role in Alzheimer's disease (AD) pathogenesis and its interaction with cell membranes in known to promote mutually disruptive structural perturbations that contribute to amyloid deposition and neurodegeneration in the brain. In addition to protein aggregation at the membrane interface and disruption of membrane integrity, growing reports demonstrate an important role for the membrane in modulating Aß production and uptake into cells. The aim of this review is to highlight and summarize recent literature that have contributed insight into the implications of altered membrane composition on amyloid precursor protein (APP) proteolysis, production of Aß, its internalization in to cells via permeabilization and receptor mediated uptake. Here, we also review the various membrane model systems and experimental tools used for probing Aß-membrane interactions to investigate the key mechanistic aspects underlying the accumulation and toxicity of Aß in AD.